2019
DOI: 10.1039/c9cc02480h
|View full text |Cite
|
Sign up to set email alerts
|

A three-component supramolecular nanocomposite as a heavy-atom-free photosensitizer

Abstract: The preparation of a supramolecular nanocomposite containing BODIPY, tryptophan and gold nanoparticles capable of photosensitized generation of singlet oxygen is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 39 publications
3
29
0
Order By: Relevance
“…In NC1 , the position of H c is similar to that in Trp which indicates that tryptophan moieties are displaced by B1 thereby implying strong interaction of B1 with gold. We had reported significant changes in the 19 F NMR spectrum of NC1 as compared to B1 which substantiates strong interaction of B1 with gold [35] . Further, it is proposed that hydrogen bonds are formed between the aromatic −NH of the tryptophan and a fluorine atom of the −BF 2 unit of B1 .…”
Section: Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…In NC1 , the position of H c is similar to that in Trp which indicates that tryptophan moieties are displaced by B1 thereby implying strong interaction of B1 with gold. We had reported significant changes in the 19 F NMR spectrum of NC1 as compared to B1 which substantiates strong interaction of B1 with gold [35] . Further, it is proposed that hydrogen bonds are formed between the aromatic −NH of the tryptophan and a fluorine atom of the −BF 2 unit of B1 .…”
Section: Resultssupporting
confidence: 62%
“…It is noteworthy that the singlet oxygen quantum yield of NC1 and NC3 were reasonably high (0.46 and 0.42, respectively) and were comparable to that of methylene blue (Figure S20). It was also observed that Au NP was capable of generating singlet oxygen under similar conditions but the singlet oxygen quantum yield was significantly lower (φ ▵ =0.027) [35] …”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations